The Influence of Part-Time Jobs and Time Management on the Academic Achievement of Students at Universitas PGRI Jombang - Rega Arista; Munawaroh (Jurnal Pendidikan Edutama, 2026)
The phenomenon of students working while studying continues to increase due to economic needs, the desire to gain work experience, and the demand for financial independence. This study aims to analyze the influence of part-time jobs and time management on the academic achievement of students at PGRI University Jombang. The study uses a quantitative approach with a survey method involving 85 students who have part-time jobs. The data were analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that part-time jobs and time management have a positive and significant effect on academic achievement, both partially and simultaneously, with a significance value of 0.000. The Adjusted R Square value of 0.693 shows that these two variables can explain 69.3% of the variation in academic achievement. These findings indicate that effective management of work and time can support the improvement of students' academic performance.